Standarisasi Parameter Spesifik dan Non Spesifik Ekstrak Etanol Daun Gatal (Laportea decumana (Roxb.) Wedd) Sebagai Bahan Baku Obat Herbal Terstandar - Mewar, Djulfikri; As'ad, Muh. Fadhil (FORIKES, 2023)
Laportea decumana (Roxb) Wedd is a plant that belongs to the urticaceae family which is used by the people of Maluku as a traditional medicine to treat various ailments such as mild strokes, anti-pain, headaches, aching rheumatic pains and stomachaches. This study aimed to standardize the specific and non-specific parameters of the Maluku Laportea decumana extract, in order to meet the requirements as a standardized herbal medicine raw material. Standardization was carried out on certain parameters including the determination of the organoleptic extract, dissolved compound content, chemical content of the extract using thin layer chromatography, while the non-specific parameters of the extract included water content, residual ash content, and heavy metal contamination. Laportea decumana extract was a viscous extract, green in color, had a characteristic odor, tastes bitter and spicy. The thin layer chromatography profile of the extract showed the presence of flavanoid, phenolic, saponin and essential oil compounds. The range of water-soluble compound content = 11.57%, ethanol-soluble compound content = 8.31%, drying shrinkage = 0.46%, water content = 3.72%, total ash content = 36.84%, acid insoluble ash content = 6.00%, lead (Pb) metal contamination = 3.17 µg/g and cadmium metal contamination <0.01 µg/g.Keywords: Laportea decumana; specific parameters; nonspecific parameters; traditional medicine ABSTRAK Laportea decumana (Roxb) Wedd adalah tanaman yang termasuk keluarga urticaceae yang digunakan oleh masyarakat Maluku sebagai obat tradisional untuk mengobati berbagi penyakit seperti stroke ringan, anti nyeri, sakit kepala, pegal linu dan sakit perut. Penelitian ini bertujuan untuk menstandarisasi parameter spesifik dan non spesifik ekstrak Laportea decumana Maluku, dalam rangka memenuhi persyaratan sebagai bahan baku obat herbal terstandar. Standardisasi dilakukan dilakukan terhadap parameter-parameter tertentu meliputi penetapan organoleptik ekstrak, kandungan senyawa terlarut, kandungan kimia ekstrak menggunakan kromatografi lapis tipis, sedangkan parameter non spesifik ekstrak meliputi kadar air, kadar abu residu, dan cemaran logam berat. Ekstrak Laportea decumana merupakan ekstrak kental, berwarna hijau, berbau khas, berasa pahit dan pedas. Profil kromatografi lapis tipis ekstrak menunjukkan adanya senyawa flavanoid, fenolik, saponin dan minyak atsiri. Kisaran kadar senyawa yang larut dalam air = 11,57%, kadar senyawa yang larut dalam etanol = 8,31%, susut pengeringan = 0,46%, kadar air = 3,72%, kadar abu total = 36,84%, kadar abu tidak larut asam = 6,00%, cemaran logam timbal (Pb) = 3,17 µg/g dan cemaran logam cadmium <0,01 µg/g.Kata kunci: Laportea decumana; parameter spesifik; parameter nonpesifik; obat tradisional